Stress perceived by nurses in the emergency and hospitalization area in hospitals in North - Del Rosario Retuerto, Fatima Rossana (2021)
Objective: Determine the level of stress perceived by nurses in the emergency and hospitalization area in hospitals in North Lima during the COVID-19 pandemic. Materials and methods: a quantitative, descriptive and cross-sectional study was carried out. The population consisted of 114 nurses from the hospitalization and emergency service. To assess stress, the instrument called The Nursing Stress Scale (NSS) was used. Results: in relation to stress in nursing professionals, the low level prevailed with 57% (n = 65), followed by the medium level 41.2% (n = 47) and the high level with 1.8% (n = 2). Regarding the dimensions, in the physical environment the medium level predominated with 48.2% (n = 55), in the psychological environment the low level predominated with 57% (n = 65) and in the social environment in the hospital the low level with 92.1% (n = 105). The dimension with the highest stress score was the physical environment with 6.1% (n = 7). Conclusions: The majority of nursing professionals had a low level of stress. Regarding the dimensions, in the psychological and social environment they had a low level, while in the physical environment they had a medium level.